Data from: Evaluation of a novel NanoQuil vaccine against S. aureus-induced mastitis - Dahlberg, Josef (Swedish University of Agricultural Sciences, 2026)
The study was a clinical trial for a new mastitis vaccine run as a comparative study with Startvac as control. In total data from 199 lactations from 144 cows are included. Milk yield and somatic cell count (SCC) was the main evaluation points. This deposit contains raw data for the manuscript "Evaluation of a novel NanoQuil vaccine against S. aureus-induced mastitis".
"vaccineringar" file includes vaccination dates for all cows (dose 1, 2 (and 3 if relevant)).
"Kalvningar_2021-10-01-2023-05-12" includes actual calving date.
"Provmjolkningar_2021-10-01-2023-11-24" includes production data on milk yield and SCC.

Studien var en klinisk prövning av ett nytt mastit-vaccin som genomfördes som en jämförande studie med Startvac som kontroll. Totalt ingår data från 199 laktationer från 144 kor. Mjölkavkastning och somatiskt celltal (SCC) var de huvudsakliga utvärderingspunkterna. Denna deposition innehåller rådata till manuskriptet "Utvärdering av ett nytt NanoQuil-vaccin mot S. aureus-orsakad mastit".
"vaccineringar"-filen inkluderar vaccinationsdatum för alla kor (dos 1, 2 (och 3 om relevant)).
"Kalvningar_2021-10-01-2023-05-12" inkluderar faktiskt kalvningsdatum.
"Provmjolkningar_2021-10-01-2023-11-24" inkluderar data om mjölkavkastning och SCC.
Data från: Utvärdering av ett nytt NanoQuil vaccin mot S. aureus-orsakad mastit
Keywords: Mastitis, Bovine; Juverinflammation; ISCOMs; ISCOMer; Clinical Trial, Phase III; Klinisk prövning, fas III [Publikationstyp]; Adjuvants, Vaccine; Adjuvanterat vaccin; Swedish red breed, for dairy production; SRB; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Biotechnology; Bioteknik; Clinical Science; Klinisk vetenskap; Animal and Dairy Science; Husdjursvetenskap; Other Veterinary Science; Annan veterinärmedicin